Extent of interocular (a)symmetry based on the metabolomic profile of human aqueous humor - Pietrowska, Karolina; Dmuchowska, Diana Anna; Godlewski, Adrian; Grochowski, Emil Tomasz; Wojnar, Malgorzata; Gosk, Wioleta; Konopinska, Joanna; Kretowski, Adam; Ciborowski, Michal (Frontiers in Molecular Biosciences, 2023)
Aims Interocular comparison of the metabolomic signature of aqueous humor (AH) was performed. The aim of the study was to quantitatively evaluate the symmetry in concentrations of various metabolites belonging to different categories. Methods The study included AH samples from 23 patients, 74.17 ± 11.52 years old, undergoing simultaneous bilateral cataract surgery at the Ophthalmology Department of the Medical University of Bialystok, Poland. Liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS)-based targeted metabolomics and lipidomics analyses of AH samples were performed using the AbsoluteIDQ® p180 kit. Out of 188 metabolites available in the kit, 67 were measured in the majority (>70%) of the samples: 21/21 amino acids, 10/22 biogenic amines, 9/40 acylcarnitines, 0/14 lysophosphatidylcholines, 21/76 phosphatidylcholines, 5/15 sphingolipids, and 1/1sum of hexoses. Results The comparison of both eyes revealed that the concentrations of metabolites did not differ significantly (p<0.05) except for taurine (p=0.037). There was moderate-to-strong positive interocular correlation (r>0.5) between most metabolites regarding concentration. This was confirmed by the high intraclass correlation coefficient (ICC) values of different levels, which varied for the different metabolites. However, there were exceptions. Correlations were not significant for 2 acylcarnitines (tiglylcarnitine and decadienylcarnitine) and 3 glycerophospholipids (PC aa C32:3, PC aa C40:2, and PC aa C40:5). Conclusions With a few exceptions, a single eye was found to be representative of the fellow eye in terms of the concentration of most of the analyzed metabolites. The degree of intraindividual variability in the AH of fellow eyes differs for particular metabolites/metabolite categories.